Estratégias de referenciação em textos narrativos de alunos surdos participantes do Projeto Oficina de Leitura e escrita de português - RIBEIRO, Floriete Assunção (2025)
This study aims to analyze textual production the deaf students from the referral based in the studies of the textual linguistics. As well as to identify the mechanisms of referral anaphoric, to describe the anaphora found in the texts and to classify the mechanisms of referral anaphoric in the narrative texts written in Portuguese, as second language, of four deaf of the extension Project, Workshop of Reading and Writing in Portuguese for the Deaf (OLEPS) / ILC/UFPA. Thus, so this research is treated of a qualitative approach that is characterized by observing, to register, to classify and to analyze data made available by the project. Being also, an empiric- inductive research that was based in bibliographical researches, revision of the literature in the area of the textual linguistics and collection of data in the project OLEPS. That organize the text in five moments: The first refers to the introduction; in the second, the theoretical grounding; soon afterwards methodological procedures, later results of Corpus analyzes and final considerations. As main results are pointed the analysis of referral strategies in that was noticed that the deaf ones make uses of the anaphora in their texts, being evidenced a differentiated construction of the texts of listeners, with strong influence of the language of signs.